DEVELOPING LEARNING MATERIALS FOR SPECIFIC PURPOSES - Y. M. Harsono (TEFLIN Journal: A publication on the teaching and learning of English, 2007)
Abstract: Teaching/learning materials is one of the very crucial elements that has to exist to conduct teaching/learning activities. This paper describes teaching/learning materials development for ESP. The description includes the definition, the principles, the procedure, and the practical undertaking of the materials development with the case of developing learning materials for ESP.